Fibronectin fragments modulate monocyte VLA-5 expression and monocyte migration - Trial, JoAnn (American Society for Clinical Investigation, 1999)
To identify the mechanisms that cause monocyte localization in infarcted myocardium, we studied the impact of ischemia-reperfusion injury on the surface expression and function of the monocyte fibronectin (FN) receptor VLA-5 (α(5)β(1) integrin, CD49e/CD29). Myocardial infarction was associated with the release of FN fragments into cardiac extracellular fluids. Incubating monocytes with postreperfusion cardiac lymph that contained these FN fragments selectively reduced expression of VLA-5, an effect suppressed by specific immunoadsorption of the fragments. Treating monocytes with purified, 120-kDa cell-binding FN fragments (FN120) likewise decreased VLA-5 expression, and did so by inducing a serine proteinase–dependent proteolysis of this β(1) integrin. We postulated that changes in VLA-5 expression, which were induced by interactions with cell-binding FN fragments, may alter monocyte migration into tissue FN, a prominent component of the cardiac extracellular matrix. Support for this hypothesis came from experiments showing that FN120 treatment significantly reduced both spontaneous and MCP-1–induced monocyte migration on an FN-impregnated collagen matrix. In vivo, it is likely that contact with cell-binding FN fragments also modulates VLA-5/FN adhesive interactions, and this causes monocytes to accumulate at sites where the fragment concentration is sufficient to ensure proteolytic degradation of VLA-5. J. Clin. Invest. 104:419–430 (1999).